2016
DOI: 10.1139/apnm-2016-0122
|View full text |Cite
|
Sign up to set email alerts
|

“Weighing” the effects of exercise and intrinsic aerobic capacity: are there beneficial effects independent of changes in weight?

Abstract: It has been known for centuries that regularly performed exercise has beneficial effects on metabolic health. Owing to its central role in locomotion and the fact that it accounts for a large majority of whole-body glucose disposal and fatty acid oxidation, the effects of exercise on skeletal muscle has been a central focus in exercise physiology research. With this being said it is becoming increasingly well recognized that both adipose tissue and liver metabolism are robustly modified by exercise, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…As PCOS is often associated with obesity, concomitant insulin resistance, and hyperinsulinemia, weight reduction and lifestyle change are considered important in overweight women with PCOS with anovulatory infertility . Weight reduction reduces hyperinsulinemia and insulin resistance, and increased physical activity increases insulin sensitivity . This improves the hormonal imbalance in the ovary and reduces androgen dominance .…”
Section: Resultsmentioning
confidence: 99%
“…As PCOS is often associated with obesity, concomitant insulin resistance, and hyperinsulinemia, weight reduction and lifestyle change are considered important in overweight women with PCOS with anovulatory infertility . Weight reduction reduces hyperinsulinemia and insulin resistance, and increased physical activity increases insulin sensitivity . This improves the hormonal imbalance in the ovary and reduces androgen dominance .…”
Section: Resultsmentioning
confidence: 99%
“…Using an animal model of high‐ and low‐capacity running, or equivalently, high‐ and low‐aerobic capacity (Garton et al. ; Thyfault and Wright ), previous studies demonstrated that both maintaining high oxidative capacity and improving oxidative capacity via exercise protects against structural and functional consequences due to high‐fat diet induced metabolic challenge. Mice that are selectively bred for high aerobic capacity demonstrate less intramuscular lipid in the medial gastrocnemius when given a high‐fat diet compared to low‐aerobic capacity animals (Noland et al.…”
Section: Discussionmentioning
confidence: 99%
“…Also, inflammation has been shown to induce peripheral insulin resistance as well as β‐cell dysfunction . Several studies have indicated that both GLP‐1 receptor agonists and exercise have anti‐inflammatory effects. The pronounced effect on glycaemic control during the exercise plus liraglutide group, may to some extent, be explained by the well‐known anti‐inflammatory effects of both treatment methods.…”
Section: Discussionmentioning
confidence: 99%